Human Infections by Non–Rodent-Associated Hantaviruses in Africa. (6th September 2016) - Heinemann, Patrick; Tia, Mélanie; Alabi, Abraham; Anon, Jean-Claude; Auste, Brita; Essbauer, Sandra; Gnionsahe, Apollinaire; Kigninlman, Holo; Klempa, Boris; Kraef, Christian; Kruger, Nadine; Leendertz, Fabian H.; et al.
Abstract: Various hantaviruses have been discovered in unconventional hosts (shrews and bats) in Africa. Up to now, it was unknown whether these viruses pose a threat for human health. In this study, using newly established serological assays, we demonstrated evidence of shrew-borne hantavirus infections in humans from Côte d'Ivoire and Gabon.